2020
DOI: 10.15252/embj.2020104870
|View full text |Cite
|
Sign up to set email alerts
|

HIV ‐1 capsids mimic a microtubule regulator to coordinate early stages of infection

Abstract: While the microtubule end-binding protein, EB1 facilitates early stages of HIV-1 infection, how it does so remains unclear. Here, we show that beyond its effects on microtubule acetylation, EB1 also indirectly contributes to infection by delivering the plus-end tracking protein (+TIP), cytoplasmic linker protein 170 (CLIP170) to the cell periphery. CLIP170 bound to intact HIV-1 cores or in vitro assembled capsid-nucleocapsid complexes, while EB1 did not. Moreover, unlike EB1 and several other +TIPs, CLIP170 en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 76 publications
0
29
0
Order By: Relevance
“…Supporting these findings, reconstitution of endogenous reverse transcription in a cell-free system followed by cryo-electron tomographic imaging has recently suggested that capsid uncoating does not occur in an all-or-none fashion but rather as a “local lattice rupture” where the initial stages involve the loss of relatively small surface patches, through which loops of the growing viral double-stranded cDNA could extrude [ 51 ]. Although these recent in vitro studies do not address the hotly debated question of when and where reverse transcription and uncoating occur in infected cells [ 52 55 ], they are in line with the thinking of several groups that suggest that reverse transcription and uncoating are complex processes that begin in the cytoplasm, termed “partial uncoating”, and complete inside the nucleus [ 32 , 42 , 46 , 47 , 56 75 ]. Indeed, partial loss of CA protein during cytoplasmic transport of HIV-1 cores to the nucleus has been visualized by the Hope lab for particles that go on to successfully deliver and express reporter genes [ 47 ].…”
Section: The Contentious Topic Of Cytoplasmic Versus Nuclear Uncoatingmentioning
confidence: 95%
See 1 more Smart Citation
“…Supporting these findings, reconstitution of endogenous reverse transcription in a cell-free system followed by cryo-electron tomographic imaging has recently suggested that capsid uncoating does not occur in an all-or-none fashion but rather as a “local lattice rupture” where the initial stages involve the loss of relatively small surface patches, through which loops of the growing viral double-stranded cDNA could extrude [ 51 ]. Although these recent in vitro studies do not address the hotly debated question of when and where reverse transcription and uncoating occur in infected cells [ 52 55 ], they are in line with the thinking of several groups that suggest that reverse transcription and uncoating are complex processes that begin in the cytoplasm, termed “partial uncoating”, and complete inside the nucleus [ 32 , 42 , 46 , 47 , 56 75 ]. Indeed, partial loss of CA protein during cytoplasmic transport of HIV-1 cores to the nucleus has been visualized by the Hope lab for particles that go on to successfully deliver and express reporter genes [ 47 ].…”
Section: The Contentious Topic Of Cytoplasmic Versus Nuclear Uncoatingmentioning
confidence: 95%
“…Recent work has shed light on how HIV-1 particles are capable of engaging several different classes of +TIPs to regulate MT dynamics together with trafficking and uncoating of viral cores, which occurs at least in part through mimicry of EB1. Beyond its direct role in regulating MT dynamics that control infection, EB1 was also found to indirectly contribute to early HIV-1 infection by delivering +TIPs such as cytoplasmic linker protein-170 (CLIP170) to the cell periphery [ 75 ] (Table 1 ). CLIP170 was shown to function differently to EB1 or other previously identified +TIPs discussed above, in that it regulates infection without significantly affecting the formation of stable MTs.…”
Section: Hiv-1 Capsid Mimicry Of Eb1mentioning
confidence: 99%
“…A number of cellular factors that participate in microtubule-dependent transport mechanisms have been shown to interact with HIV-1 CA (see [ 59 ] and [ 60 ] for recent reviews), including microtubule-associated proteins 1 (MAP1) [ 61 ], fasciculation and elongation factor zeta 1 (FEZ1) [ 62 , 63 ], diaphanous 2 (Dia2) [ 64 ], Bicaudal D2 (BICD2) [ 65 , 66 ], cytoplasmic linker-associated protein 2 (CLASP2) [ 67 ], and cytoplasmic linker protein 170 (CLIP170) [ 68 ]. Although these studies established contributions from these binding factors to HIV-1 retrograde movement within cells, it is unclear if infection would require the viral core to bind to all of these proteins simultaneously.…”
Section: The Trip To the Nucleusmentioning
confidence: 99%
“…In addition to EB1, diaphanous-related formins (DRFs) have been shown to facilitate microtubule stabilization and assist in the intracellular trafficking and timed disassembly of capsid by interacting directly with the capsid core to coordinate these processes [ 84 ]. Such findings suggest a mechanism for HIV-1 to highjack host cell machinery to achieve movement in the cell [ 85 ].…”
Section: Function Of the Hiv-1 Capsidmentioning
confidence: 99%